2017
DOI: 10.7150/thno.18922
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Imaging and Anti-inflammatory Therapy of Muscle and Tendon Injuries Using Polymer Nanoparticles

Abstract: Ultrasonography is a reliable diagnostic modality for muscle and tendon injuries, but it has been challenging to find right diagnosis of minor musculoskeletal injuries by conventional ultrasonographic imaging. A large amount of hydrogen peroxide (H2O2) are known to be generated during tissue damages such as mechanical injury and therefore H2O2 holds great potential as a diagnostic and therapeutic marker for mechanical injuries in the musculoskeletal system. We previously developed poly(vanillyl alcohol-co-oxal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…Aryl oxalates may react with H 2 O 2 to form 1,2-dioxetanediones, which can be rapidly converted into carbon dioxide (CO 2 ) and phenols. Thus, aryl oxalate ester bonds in polymerized nanoparticles may induce degradation and then release the payload when exposed to H 2 O 2 to achieve intelligent delivery of drugs (Kim et al, 2017).…”
Section: Other Polymer Systems Aryl Oxalate-containing Polymersmentioning
confidence: 99%
“…Aryl oxalates may react with H 2 O 2 to form 1,2-dioxetanediones, which can be rapidly converted into carbon dioxide (CO 2 ) and phenols. Thus, aryl oxalate ester bonds in polymerized nanoparticles may induce degradation and then release the payload when exposed to H 2 O 2 to achieve intelligent delivery of drugs (Kim et al, 2017).…”
Section: Other Polymer Systems Aryl Oxalate-containing Polymersmentioning
confidence: 99%
“…Because of easy detection, low cost and no radiation hazard, it has been used as a screening method for liver disease. Conventional ultrasound contrast agents are microbubbles composed of a shell material of lipids and proteins and a gas core, whose diameter is 1-8 μm [209][210][211]. However, there exist undesired imaging https://doi.org/10.1007/s40820-020-00550-x © The authors defects, such as poor blood vessel stability, short echo persistence, and difficulty in penetrating surrounding tissues [212].…”
Section: Ultrasound Imagingmentioning
confidence: 99%
“…Analogous to ketalized maltodextrin nanoparticles, hydrogen peroxide-activatable peroxalate polymer can produce CO 2 in a H 2 O 2 -induced manner. It was reported that the peroxalate polymers could act as both the ultrasound imaging agent for H 2 O 2 -related inflammatory diseases [ 210 , 211 ], and the backbone of polymeric prodrugs for biologically active compounds [ 215 , 216 ]. Curcumin has potent antioxidant and ROS scavenging pharmacological effects because of the capacity of providing hydrogen atoms [ 217 ].…”
Section: Nanobiomaterials As Imaging Agents For Acute Liver Failure Theranosticsmentioning
confidence: 99%
“…Protein expression of caspase-3, Bcl-2, and Bax confirms the anti-apoptotic potential for the PVAX particle formulation. The integration of diagnosis and therapeutic nature of PVAX, using ultrasound imaging of musculoskeletal injuries was tested and proved to be an added advantage to age-related skeletal muscle dysfunction [ 46 ].…”
Section: Bio Compatibility Of Polyoxalate and Copolyoxalatesmentioning
confidence: 99%